The effect of reclaimed asphalt pavement (RAP) proportion on strength properties of a full depth recycling pavement / Roziawati Razali - Razali, Roziawati (2010)
Reclaimed Asphalt Pavement (RAP) is the term given to the removed and/or reprocessed pavement materials containing asphaltic concrete. Cold in-place recycling (CIPR) is the processing and treatment with bituminous and/or chemical additives of existing Reclaimed Asphalt Pavement (RAP) without heating to produce a restored pavement layer. The pavement recycling using CIPR technique may either full depth recycling or partial recycling depending on the use of base materials. Full depth recycling may involved the use of base material as a part of recycled pavement layer and partial recycling only used RAP material to rebuild the new road. One of the advantages of the Cold in Place Recycling (CIPR) is cost savings of up to 40 percent over conventional techniques and also environmentally responsible method of asphalt pavement reconstruction. Pavement recycling was first introduced about half a century ago in the most of West Country (e.g. United State America, South Africa etc). but the technology is relatively new in Malaysia. Currently in Malaysia, there is no documented guidelines/specification on the optimum RAP portion in stabilized recycled pavement mixes. The Road Engineering Association of Malaysia (REAM) had developed the Specification for Cold in Place Recycling but does not specify the requirement of RAP content for full depth pavement recycling. This study aims are to evaluate the strength properties of a full depth recycling pavement with different RAP proportions, and hence deduce the optimum reclaimed asphalt pavement proportion content in recycled mix design . There were four (4) RAP proportions and crush stone aggregate combinations which were 0% RAP, 25% RAP, 50% RAP and 75% RAP from the total sample weight using one single grading. Proctor Test method was first carried out to determine the optimum moisture content at every RAP contents. In order to determine the optimum cement and binder content and binder content, similarly, 1.5%, 2.0% and 2.5% cement and 2%,3%, 4%,5% and 6% bitumen emulsion by total weight were prepared at every RAP content. The samples were then tested for Marshall Stability, Density and Flow test for determination of the optimum bitumen emulsion 'and cement content of the recycled mixes at every RAP contents. The result of maximum stability, flow and density versus bitumen emulsion content were plotted to determine the optimum bitumen emulsion and cement content for every RAP contents. Samples were prepared at the optimum moisture content, optimum bitumen emulsion and cement content and tested for Unconfined Compressive Strength, Indirect Tensile Strength and Resilient Modulus at every RAP proportions to determine the performance of the recycled mixes.